In vivo evaluation of [11C]TMI, a COX-2 selective PET tracer, in baboons. Issue 23 (15th December 2018) - Kumar, J.S. Dileep; Zanderigo, Francesca; Prabhakaran, Jaya; Rubin-Falcone, Harry; Parsey, Ramin V.; Mann, J. John.
Graphical abstract: Highlights: Induced COX-2 expression is one of the pathophysiology of inflammation. Upregulation of COX-2 expression is a biomarker for diseases. [ 11 C]TMI, a COX-2 PET tracer exhibit brain penetration and retained in baboon brain. Radiotracer exhibit specific binding in baboon brain. Abstract: Overexpression of Cyclooxygenase-2 (COX-2) enzyme is associated with the pathogenesis of inflammation, cancers, stroke, arthritis, and neurological disorders. Because of the involvement of COX-2 in these diseases, quantification of COX-2 expression using Positron Emission Tomography (PET) may be a biological marker for early diagnosis, monitoring of disease progression, and an indicator of effective treatment. At present there is no target-specific or validated PET tracer available for in vivo quantification of COX-2. The objective of this study is to evaluate [ 11 C]TMI, a selective COX-2 inhibitor (Ki ≤ 1 nM) in nonhuman primates using PET imaging. PET imaging in baboons showed that [ 11 C]TMI penetrates the blood brain barrier (BBB) and accumulates in brain in a somewhat heterogeneous pattern. Metabolite analyses indicated that [ 11 C]TMI undergoes no significant metabolism of parent tracer in the plasma for baseline scans, however a relative faster metabolism was found for blocking scan. All the tested quantification approaches provide comparable tracer total distribution volume (VT ) estimates in the range of 3.2–7 (mL/cm 3 ). We observed about 25% lower VT values in blocking studies with meloxicam, a nonselective COX-2 inhibitor, compared to baseline [ 11 C]TMI binding. Our findings indicate that [ 11 C]TMI may be a suitable PET tracer for the quantification of COX-2 in vivo. Further experiments are needed to confirm the potential of this tracer in COX-2 overexpressing models for brain diseases.